Inflammatory bowel disease and the risk of all caused or specific fracture: a meta-epidemiologic study - Wang, Weiren; Liu, Hongfei; Wei, Wei; Zhou, Guangzhi; Yu, Bohan; Xue, Fumin; Kang, Siwen; Tai, Dongxu (Frontiers in Endocrinology, 2026)
ObjectiveTo evaluate the overall and site-specific fracture risk in individuals with IBD through a meta-epidemiologic approach, synthesizing data from cohort studies and providing a comprehensive analysis of fracture risk at different anatomical sites.MethodsFollowing PRISMA 2020 guidelines, we systematically searched PubMed, Embase, and the Cochrane Library (inception to April 2025) for cohort studies reporting fracture risk in IBD patients. Eligible studies provided relative risk (RR) and 95% confidence interval(CI) for all-cause or site-specific fractures. Two reviewers independently screened records, extracted data, and assessed study quality using the Newcastle-Ottawa Scale (NOS). Random-effects meta-analysis, sensitivity/subgroup analyses, and publication bias assessment (funnel plots, Egger’s test) were performed.ResultEleven cohort studies (4 prospective, 7 retrospective) from multiple countries were included, involving 2,102 to 54,591 IBD patients. NOS scores ranged from 5 to 8, indicating moderate to high study quality. Pooled analysis showed a 13% increased risk of all-cause fractures in IBD patients (RR = 1.13, 95% CI: 1.03–1.24; I²=70.8%, p<0.001). Subgroup analysis revealed higher fracture risks in Crohn’s disease (CD: RR = 1.23, 95% CI: 1.21–1.25) compared to ulcerative colitis (UC: RR = 1.16, 95% CI: 1.13–1.19). Site-specific risks were significantly higher for rib (RR = 1.24, 95% CI: 1.08–1.42; I²=0%, p=0.978), hip (RR = 1.39, 95% CI: 1.22–1.59; I²=54.2%, p=0.053), upper limb (RR = 1.46, 95% CI: 1.18–1.82; I²=94.6%, p<0.001), and lower limb fractures (RR = 1.60, 95% CI: 1.36–1.88; I²=75.4%, p<0.001). Sensitivity analyses confirmed the robustness of the results, and funnel plots/Egger’s test indicated no significant publication bias (p=0.612).ConclusionIBD is associated with increased risks of all-cause and site-specific fractures, particularly in CD patients and lower limb fractures. These findings underscore the need for targeted bone health monitoring in IBD management.Systematic review registrationPROSPERO, identifier: CRD420251038879.